DEVELOPING ENGLISH PRINTED MATERIAL ON THEME OF OCCUPATION FOR EARLY YOUNG LEARNERS AT PAUD TERPADU JOY KIDS MAKASSAR - Yusmiyati, Eka; Kamsinah, Kamsinah; Nurpahmi, Sitti (English Language Teaching for EFL Learners Journal, 2021)
The main objective of this research is to develop English language materials for early young learners. This research was conducted at PAUD Terpadu Joy Kids Makassar. This research developed "Occupation" material with the sub-theme of "firefighter." The Research and Development model implemented in this study was ADDIE model in developing the material. The preliminary study results in this study show that English is not a compulsory subject but only an interlude. Therefore, researchers developed English language material following the applicable curriculum. The development of material in this study emphasized vocabulary recognition. Teachers and students can use the products that researchers would produce to carry out English learning activities.